Production of Ethyl Esters from Jatropha Oil using Wet Ethanol - Taggar, Monica Sachdeva; Soni, Rajesh; Singh, S. K.; Sooch, Sarbhjit Singh; Sangha, M. K. (Journal of Agricultural Engineering, 2014)
Ethanol based biodiesel prepared from plant oils is environment friendly. Ethyl esters were prepared from Jatropha curcas L. oil using wet ethanol (170, 180 and 190 proof ethanol) as reactant. The crude oil had free fatty acid contents of 6.3% and acid value of 11.2. In the present study, two methods were employed for the preparation of biodiesel. The first method involved pre-treatment of crude oil with acid catalyst, followed by base-catalysed transesterification. The second method involved acid catalysed esterification/trans-esterification of crude oil, followed by base-catalysed trans-esterification reaction. The highest recovery and per cent conversion of oil into ethyl ester was achieved with acid catalyst pre-treatment for 1h using 190 proof ethanol as reactant, followed by base catalysed reaction using anhydrous ethanol (199.8 proof) .The concentration of KOH used as catalyst was 2.5% (w/v of oil). The recovery and conversion of oil into ethyl ester were 55.1 and 90%, respectively. The cost of ethyl esters (biodiesel), thus prepared, was estimated to be slightly lower as compared to the conventional process used for preparation of ethyl esters.